American Influence in Boku no Hero Academia: A Semiotic Study - Sujiwa, Krisna (Fakultas Ilmu Budaya, Universitas Jambi, 2025)
This study examines the influence of American culture on Japanese manga, with a focus on Boku no Hero Academia (BNHA). It explores how American superhero tropes, values, and ideologies are incorporated into Japanese media, reflecting broader themes of globalization and cultural hybridization. Using Roland Barthes' semiotic theory, the research analyzes BNHA's visual, narrative, and thematic elements to uncover both denotative and connotative meanings of American influences. The qualitative research approach relies on primary data from the manga, focusing on character designs, dialogue, and institutional structures. Key findings show that characters like All Might, Star and Stripe, Best Jeanist, Present Mic, and Snipe embody American cultural archetypes, such as superhero and cowboy imagery. All Might symbolizes American exceptionalism, while Star and Stripe reflects militaristic ideals. The study reveals how BNHA blends American influences with Japanese storytelling, contributing to global discussions on cultural exchange in popular media and illustrating the hybrid nature of modern narratives. Abstrak Penelitian ini mengkaji pengaruh budaya Amerika pada manga Jepang, dengan fokus pada Boku no Hero Academia (BNHA). Penelitian ini mengeksplorasi bagaimana tropes, nilai, dan ideologi superhero Amerika diintegrasikan ke dalam media Jepang, mencerminkan tema-tema globalisasi dan hibridisasi budaya. Menggunakan teori semiotik Roland Barthes, penelitian ini menganalisis elemen visual, naratif, dan tematik BNHA untuk mengungkap makna denotatif dan konotatif dari pengaruh Amerika. Pendekatan penelitian kualitatif ini mengandalkan data primer dari manga, dengan fokus pada desain karakter, dialog, dan struktur institusional. Temuan utama menunjukkan bahwa karakter-karakter seperti All Might, Star and Stripe, Best Jeanist, Present Mic, dan Snipe mewakili arketipe budaya Amerika, seperti ikonografi superhero dan mitologi koboi. All Might, misalnya, melambangkan eksseptionalisme Amerika, sementara Star and Stripe mencerminkan ideologi militeristik. Penelitian ini mengungkap bagaimana BNHA menggabungkan pengaruh Amerika dengan penceritaan Jepang, berkontribusi pada diskusi global tentang pertukaran budaya dalam media populer dan menggambarkan sifat hibrida dari narasi modern.